Two ways of dealing with scientific fraud - Polšek, Darko (1997)
Criticism of science has so far followed two paths: by debunking fraudulent research, or by debunking pseudo-scientific claims. People believe weird things because high and hard sciences give them reasons to. Such high-science claims give them reasons to do so.
Projekt MZOS
ENG